Planning and Analysis of Economic Feasibility of Hybrid Solar Power Plant in Bekasi City Residential - Stepanus Stepanus; Leonard Lisapaly; Andrew Paul Wijaya; Robinson Purba (G-Tech: Jurnal Teknologi Terapan, 2024)
This study discusses planning the Economic Feasibility of a Hybrid Solar Power Plant for consumer homes from PLN customers who are included in non-subsidized customers. Planning is carried out for middle and upper-scale households in Bekasi City. A household segment that uses a large amount of energy every month, high electricity bills every month makes consumers have to save energy so they can save on monthly bills. With the rapid increase in population growth, the energy demand is higher, so the electricity price from consumers will also increase. In addition, hazardous substances produced from using fossil energy sourced from PLN are one of the primary research focuses. From the simulation results using HOMER, it was found that installing PLTS can reduce CO2 emission levels by 33% with an NPC saving cost of Rp. 67.2 million, the energy that can be generated from the 4 Pv and Inverter configuration is 3,172 kW/yr with a COE of Rp.499.95.